Phytoestrogen intake and cardiovascular risk markers in Bangladeshi postmenopausal women. - Saleh, F; Afnan, F; Ara, F; Yasmin, S; Nahar, K; Khatun, F; Ali, L (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 219-225 The abstract of this article is available on the PubMed website